2020
DOI: 10.1097/meg.0000000000001661
|View full text |Cite
|
Sign up to set email alerts
|

A ‘real-world’ analysis of risk factors for post liver transplant delirium and the effect on length of stay

Abstract: Background The development of delirium has been previously demonstrated to be associated with an increased risk of mortality and length of stay post liver transplant (LTx) with multiple risk factors being identified in previous studies. In this study, we have aimed to identify the most important variables associated with the onset of post-LTx delirium and understand the effect on length of stay (LOS). Methods All liver transplants for chronic liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…POD is a frequent and serious complication after OLT as it is closely associated with increased morbidity, mortality, and medical care expenses [8,[20][21][22]. It was demonstrated to increase hospital stay by 2-3 days and was associated with a 30-day mortality of 7-10% in recent literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…POD is a frequent and serious complication after OLT as it is closely associated with increased morbidity, mortality, and medical care expenses [8,[20][21][22]. It was demonstrated to increase hospital stay by 2-3 days and was associated with a 30-day mortality of 7-10% in recent literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between delirium and mortality is controversial. Several studies showed that delirium did not affect in-hospital or 1 year mortality with proper treatment ( 4 , 34 , 35 ). Nevertheless, Lescot et al and Wang et al reported that delirium after LT was related to in-hospital and 1 year mortality ( 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure and infection were precipitating factors. Other studies have focused on surgical patients, for instance, in patients undergoing hepatectomy ( 35 , 36 ). As in our cohort, delirium was associated with an overall increased hospital and ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%